Searching behaviour of Amitus fuscipennis: Residence time and walking activity - MANZANO, MARÍA DEL ROSARIO; VAN LENTEREN, JOOP C.; CARDONA-M., CÉSAR (Revista Colombiana de Entomología, 2003)
Knowledge about the foraging behaviour of parasitoids is essential to estimate the efficiency of biological control agents and to develop parasitoid release strategies. In this paper, the behaviour of A. fuscipennis when searching for Trialeurodes vaporariorum nymphs on bean plants was studied under laboratory conditions. The residence time and searching behaviour of A. [uscipennis were determined on plants sprayed or unsprayed with a sulphur-based fungicide, and infested or uninfested with nymphs of T.  vaporariorum. The residence time and walking activity of A. [uscipennis on infested, unsprayed plants were higher than that of uninfected or sprayed plants. The residence time of A. fuscipennis was prolonged by both, encounters with unparasitized hosts and by feeding from the plant.  Results suggest that:  1) residence time was reduced on fungicide sprayed plants,  indicating that the fungicide disturbed A. fuscipennis,  when A. fuscipennis  is used within an integrated  Pest Managment (IPM) system  for A. fuscipennis, special care must be taken on that the release and migration of the parasite to the crop do not happen immediately after a sulfurated fungicide has been applied. 2) Despite being a pro-ovygenic parasitoid that emerges with their life-time egg load ready to oviposit, A. fuscipennis needs to feed on the plant probably because searching for hosts demands extra energy.